1997
DOI: 10.1055/s-2007-972689
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Fitness in Patients with Headache Disorders*

Abstract: Recent studies indicate that aerobic activities might reduce severity and/or frequency of migraine attacks. The present study was intended to investigate whether physical activities and fitness (aerobic endurance, flexibility, and muscle strength endurance) as well as body composition are different in patients with headache disorders and healthy control subjects. The study included 56 patients (aged 17-64 years) with headache disorders (migraine, tension-type, cluster, analgetics abuse, and other types of head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 3 publications
0
7
0
1
Order By: Relevance
“…Headache patients turned out to be less physically fit than control subjects. However, habits such as smoking did not differ significantly between both groups …”
Section: Conflicting Inadequate or Equivocal Smoking Studiesmentioning
confidence: 78%
“…Headache patients turned out to be less physically fit than control subjects. However, habits such as smoking did not differ significantly between both groups …”
Section: Conflicting Inadequate or Equivocal Smoking Studiesmentioning
confidence: 78%
“…A majority of the published studies, primarily dealing with adults, found associations between headache and skipping meals, 19,20,26 high consumption of caffeine, 1,14‐16 regular smoking, 1,20,24‐27 excessive consumption of alcohol 1,20,26,28 or physical inactivity 20,22,23,31 . In contrast, there is a limited number of studies which did not report such associations between headache and skipping meals, 16 high consumption of caffeine, 21,32 regular smoking, 16,21,31 consumption of alcohol, 16,21,32 or physical inactivity 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Dietary factors, such as high consumption of coffeine, 1,13‐16 insufficient fluid intake, 17,18 or irregular intake of meals, 19,20 were identified as contributing to trigger or prolong headache attacks or headache frequency. Other lifestyle factors, such as physical inactivity, 20‐23 smoking 1,20,24‐27 or excessive consumption of alcohol, 20,26,28 were also reported to be associated with headache in adults.…”
mentioning
confidence: 99%
“…Vergleichsbeobachtungen zum Sportverhalten und Sportgewohnheiten könnten dies stützen: Neusüss et al [63] stellten bei einer Gruppe von Migränikern fest, dass diese genauso oft oder selten Sport trieben wie die Vergleichspopulation ohne Kopfschmerzen, Dooley et al [20] fanden ähn-liche Ergebnisse bei Adoleszenten.…”
Section: Zusammenfassungunclassified